The Implementation of Problem-Based Learning on Multiplication and Division Lessons in Improving Elementary School Students’ Learning Motivation - Fatayan, Arum; Safrul, Safrul; Ghani, Abd Rahman A; Ayu, Sartika (Universitas Muhammadiyah Mataram, 2022)
This study aims at increasing elementary school students’ learning motivation in multiplication and division lessons by implementing problem-based learning. This study was qualitative research. Furthermore, the research subjects were elementary school students. Results indicated that students experienced an increased motivation in multiplication and division lessons after implementing problem-based learning because they felt happy during the learning process. In addition, observations, interviews, and documentation studies showed that, with problem-based learning, many students better understood the concepts of multiplication & division and applied them in their daily life. Moreover, students thought critically in solving problems when the learning process was carried out in discussion or groups. This study proves that teachers are the key to success in a learning process and the increased student motivation. Therefore, teachers must be able to choose the right learning method for students to encourage their enthusiasm for learning.